The Role of High School Experience in College Student Leadership Development - Susan R. Komives; Matthew Johnson (Educational Considerations, 2009)
Colleges and universities have long claimed student leadership development to be a desirable college outcome. Until the latter quarter of the 20th century, college experiences that developed leadership outcomes were ill-structured, incidental or accidental, and largely only targeted students who held positional leadership roles.
Keywords: colleges; universities; academic; achievement; extracurricular; involvement The Role of High School; experience; student; leadership; development; identity